Fungsi Aktansial dalam Novel Funiculi Funicula Karya Toshikazu Kawaghuci: Kajian Naratologi A. J. Greimas - Pobela, Siti Nurhalisa; Pobela, Julianti Anamira; Rusdi, Safna; Kadir, Herson (Jurusan Pendidikan Bahasa & Sastra Indonesia, Universitas Negeri Gorontalo, 2024)
This study aims to describe the actantial scheme in Toshikazu Kawaguchi's novel Funiculi Funicula and identify the role of each actant in constructing the story's plot. The research data consists of narrative elements found in the novel, analyzed to understand the dynamics of relationships between actants based on A.J. Greimas' narratology structuralism theory. The approach used is qualitative descriptive with content analysis, fokusing on actantial functions such as sender, subject, object, helper, receiver, and opponent in the story. Data collection techniques include in-depth reading of the novel text, while data analysis is conducted by identifying and mapping each actant’s function within the narrative scheme. The results show that (1) the actantial scheme in the novel involves the Funiculi Funicula café as the sender, providing a time travel mechanism to help the main characters face their emotional conflicts; (2) the story's subjects—Fumiko kiyokawa, Kotake tokita, Yaeko Hirai, and Kei Tokita—pursue objects in the form of emotional resolution and answers to personal conflicts; (3) helpers such as the café's rules, staff, and a mysterious visitor support the subjects' journeys, while the opponent, in the form of time constraints, serves as the main challenge. This study enriches narratological research by demonstrating how A.J. Greimas' theory can be applied to understanding the narrative structure of contemporary literary works.